Association between taste perception and adiposity in overweight or obese older subjects with metabolic syndrome and identification of novel taste-related genes. Issue 6 (21st April 2019) - Coltell, Oscar; Sorlí, José V; Asensio, Eva M; Fernández-Carrión, Rebeca; Barragán, Rocío; Ortega-Azorín, Carolina; Estruch, Ramon; González, José I; Salas-Salvadó, Jordi; Lamon-Fava, Stefania; Lichtenstein, Alice H; Corella, Dolores
ABSTRACT: Background: The relation between taste perception, diet, and adiposity remains controversial. Additionally, there is a lack of knowledge on the polymorphisms influencing taste given the scarcity of genome-wide association studies (GWASs) published. Objectives: We studied the relation between perception of the basic tastes, i.e., sweet, salty, bitter, sour, and umami (separately and jointly in a "taste score"), and anthropometric measurements in older subjects with metabolic syndrome (MetS). GWASs were undertaken to identify genes associated with basic tastes and their score. Methods: Taste perception was cross-sectionally determined by challenging subjects (381 older individuals with MetS) with solutions (5 concentrations) of the basic tastes with the use of standard prototypical tastants (phenylthiocarbamide and 6- n -propylthiouracil, NaCl, sucrose, monopotassium glutamate, and citric acid, for bitter, salt, sweet, umami, and sour, respectively). Taste perception intensities were expressed on a scale. A total taste score was derived. Results: The total taste score was inversely associated with body weight, body mass index, and waist circumference ( P  < 0.05). Subjects having a total taste score higher than or equal to the median (11 points for concentration V) were less likely to be classified as obese than subjects below the median (OR: 0.36; 95% CI: 0.22, 0.59; P  < 0.001). Associations were similar, albeit less strong, for some taste qualities. In the GWASs, the highest associations were for bitter taste (rs1726866- TAS2R38, with P  = 7.74 × 10 −18 for phenylthiocarbamide and P  = 3.96 × 10 −19 for 6- n -propylthiouracil). For other tastes, several single-nucleotide polymorphisms (SNPs) exceeded the P threshold of 1 × 10 −5 . However, the top-ranked SNPs independently explained a low percentage of taste variability, hence their use as single proxies for the association between taste perception and adiposity is limited. Conclusions: We found a strong inverse association between greater taste perception and body weight, body mass index, and waist circumference in older subjects with MetS and identified some taste-related SNPs. It would be advantageous to identify additional genetic proxies for taste and to develop polygenic scores. Data used in this study were derived from the clinical trial PREDIMED PLUS at baseline, registered at http://www.isrctn.com as ISRCTN89898870.